Acute altitude induced hypoxia in a child with Down's syndrome following postoperative repair of complete atrioventricular septal defect. (13th April 2011) - Griksaitis, Michael; Ang, Claire
Abstract : The authors report the case of a 4-year-old male child with a background of Down's syndrome (Trisomy 21) and a definitive repair of a balanced complete atrioventricular septal defect (CAVSD) at 3 months of age who experienced acute pulmonary oedema at high altitude (2000 m) while on holiday with his parents. The authors discuss and review the literature on the effect of altitude on children with Down's syndrome and postoperative CAVSD repair. The authors propose that further research is needed into this area in this specific group of patients, so advice can be given to families prior to flying or travelling.